Does Work-Life Reconciliation Increase Employee Retention? The Mediating Role of Employees’ Perceived Stress - Salehi, Ali; Tremblay, Diane-Gabrielle (Relations industrielles / Industrial Relations, 2024)
Today, retaining skilled and talented employees is one of the main concerns of organizations. To this end, various policies have been considered in recent years, including policies to reconcile work with personal life. We sought to investigate the effect of work-life reconciliation on employee retention while considering the mediating role of employees’ perceived stress. In 2023, we surveyed a sample of Quebec employees who are caring for young children or other family members. In general, work-life reconciliation policies significantly increase employee retention. We also studied how employees’ perceived stress, due to work-life conflict and insufficient annual income, mediate the effect of work-life reconciliation on employee retention. Although caring for children under 18 or other family members increases employees’ perceived stress, it does not directly affect employee retention. In sum, we found that employee retention can be increased through policies that promote work-life reconciliation and thereby reduce perceived stress. Our findings have important implications and may help managers and employees implement policies to reconcile work with personal life, decrease stress, and thus increase employee retention.